2022
DOI: 10.3389/fphar.2022.948889
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and neuroprotective actions of resveratrol in cerebrovascular diseases

Abstract: Cerebralvascular diseases are the most common high-mortality diseases worldwide. Despite its global prevalence, effective treatments and therapies need to be explored. Given that oxidative stress is an important risk factor involved with cerebral vascular diseases, natural antioxidants and its derivatives can be served as a promising therapeutic strategy. Resveratrol (3, 5, 4′-trihydroxystilbene) is a natural polyphenolic antioxidant found in grape skins, red wine, and berries. As a phytoalexin to protect agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 194 publications
0
7
0
Order By: Relevance
“…N2a cells were incubated for 24 h with or without AZA-ST 1a–g or resveratrol (RSV; trans -resveratrol) at concentrations inclosing the IC50s (6.25, 12.5 and 25 µM). Vehicles (Ethanol (EtOH) for RSV; DMSO for AZA-ST) [ 4 ]: Ethanol (EtOH; 0.05%) and DMSO (0.05%); the highest concentrations of vehicles were only analyzed. The data are the mean ± standard deviation (SD) of three independent experiments performed in triplicate.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…N2a cells were incubated for 24 h with or without AZA-ST 1a–g or resveratrol (RSV; trans -resveratrol) at concentrations inclosing the IC50s (6.25, 12.5 and 25 µM). Vehicles (Ethanol (EtOH) for RSV; DMSO for AZA-ST) [ 4 ]: Ethanol (EtOH; 0.05%) and DMSO (0.05%); the highest concentrations of vehicles were only analyzed. The data are the mean ± standard deviation (SD) of three independent experiments performed in triplicate.…”
Section: Figurementioning
confidence: 99%
“…These molecules are subdivided into two groups: flavonoids and non-flavonoids [ 3 ]. Among the latter, trans -resveratrol (RSV), which belongs to the stilbene subclass, is one of the most studied polyphenols because of its numerous biological activities, including antioxidant [ 4 ], anti-inflammatory [ 5 ], anti-tumor [ 6 ], and anti-ageing activities [ 7 ]. RSV has also shown neurotrophic activities in the context of Parkinson’s disease [ 8 ] and cytoprotective activities against oxidized cholesterol derivatives (oxysterols, especially 7-ketocholesterol, mainly formed by cholesterol autoxidation [ 9 ]), often found in increased amounts in patients with age-related diseases (cardiovascular diseases, Alzheimer’s disease, and age-related macular degeneration) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gallic acid inhibits glutamate release, Ca 2+ overload, and ROS production and also has anticholinesterase activity in brain tissue, thus acting as an antioxidant and neuroprotective agent (Korani et al, 2014). Numerous studies have shown that resveratrol plays a neuroprotective role in IS by increasing antioxidant capacity and reducing oxidative stress and inflammation (Al Dera, 2017; Wang, Yu, & Wu, 2022). Resveratrol significantly improves neurological function, reduces brain infarct volume, decreases neuronal damage, and inhibits neuronal apoptosis by activating the JAK2/STAT3 and PI3K/AKT/mTOR pathways (Hou, Wang, et al, 2018).…”
Section: Potential Mechanisms Of Tcm and Its Major Bioactive Constitu...mentioning
confidence: 99%
“…Regarding proinflammatory factors, resveratrol has a positive effect on reducing interleukin-1β (IL-1β), which may alleviate neurodegenerative diseases caused by neuritis. 56,57 Resveratrol also has a remarkable hepatoprotective effect by easing the nitrosodiethylamine-induced liver damage through its anti-inflammatory effect and down-regulation of cyclooxygenase-2 (COX-2) expression. 69 Lignans are also polyphenols, and three of the four pairs of 8-O-4′-type lignan isomer present in raspberry fruit have the ability to resist Aβ aggregation, 38 which may have a potential effect on the treatment of Alzheimer's disease.…”
Section: Biological Function Of Rppsmentioning
confidence: 99%